Economic Convergence in South-Eastern Europe: Will the Financial Sector deliver? - Max Watson; Valerie Herzberg (SUERF - The European Money and Finance Forum, 2007)
The rhythm of financial development in south-eastern Europe has accelerated. In a setting of low inflation and robust growth, domestic credit and cross-border flows are expanding. This process can strengthen real convergence by supporting productivity gains that enhance competitiveness and a smooth servicing of external liabilities. But such an outcome is not guaranteed. It depends on a favourable investment climate. Otherwise a normal expansion of household borrowing and housing investment might not be balanced by rising financial support for the traded goods sector, implying weak foundations for sustained growth. EU Accession - with its potential for trade and investment integration, and an acquis-based strengthening of institutions - improves the chances of good outcomes. It also triggers accelerated financial development, including through the role of EU-15 banks. There is a setting that raises the stakes for policy: it can spur the expansion of the productive economy; but it can also magnify distortions, as seen in the proliferation of unhedged foreign currency borrowing. Prudent fiscal policies and bold structural reforms are needed to underpin the medium-term outlook for growth and forestall risks of financial stress.
Keywords: E52; E58; F33; F36; G15; G21; G28; 330; Financial stability; financial development; South Eastern Europe; the Balkans; Finanzsektor; Branchenentwicklung; Schwellenländer; Südosteuropa